Dynamic Assembly of Microspheres under an Ultrasound Field. Issue 14 (13th March 2019) - Xu, Tailin; Cheng, Guanzhi; Liu, Conghui; Li, Tianlong; Zhang, Xueji
Abstract: The assembly of micro‐nanoparticles is one of the key tasks for controlling and manipulating the structure of materials at micro/‐nanoscale. By carefully designing the ultrasound experiments and comparing the results with acoustic theories, we presented an in‐depth study of the ultrasound‐induced assembly behaviors of micro/‐nanoparticles (microparticle size≪wavelength), especially their dynamic interactions between microparticles. The whole assembly processes including floating micro/nanoparticles, single particle communication, assembly to single particle interactions, and reorganization of assembly are fully studied. A rapid response of the ultrasound‐based assembly (0.5 min) shows distinct advantages compared to those of previously used methods such as light‐, electrical‐ and temperature‐based ones. Such an efficient and effective microparticle assembly holds great promise for fabrication of complex structure of materials. Abstract : From micro to nano : Ultrasound‐induced assembly behaviors of micro/‐nanoparticles (microparticle size≪wavelength) including floating micro/nanoparticles, single particle communication, assembly to single particle interactions, and reorganization of assembly are studied and described herein.